Adoption of CSA practices in Nyando basin, western Kenya: NWO-CCAFS research project: Using climate-smart financial diaries for scaling in the Nyando basin, Kenya - Oostendorp, Remco; Asseldonk, Marcel van; Gathiaka, John; Mulwa, Richard; Radeny, Maren A.O.; Recha, John W.M.; Wattel, Cor; Wesenbeeck, Lia van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Since 2012 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has been piloting the Climate-Smart Villages (CSVs) approach in East Africa, including the Nyando basin of western Kenya, introducing a wide range of Climate-Smart Agriculture (CSA) technologies and practices. The CSA interventions were tailored to address the climate risks in Nyando, the needs and circumstances of individual farmers, and were collectively piloted with the farmers for potential adoption. In this report, we present the adoption rates of various CSA technologies and practices in Nyando since the start of the CCAFS program in 2012 up to 2020. Specifically, we address the following questions: (i) What is the rate and intensity of adoption? (ii) Are there any time trends in adoption since 2012? (iii) How is adoption distributed across farmers? (iv) How does adoption change over time at the farm level (dynamics including dis-adoption)? and (v) How does adoption intensity vary across farmer characteristics?